STRATEGY FOR MONITORING ACCOUNTABILITY OF FREE MOTOR VEHICLE TESTING SERVICES AT THE SIDOARJO PKB UPT - Yos Kurniawan; Ulul Albab; Sapto Pramono (International Journal of Multidisciplinary Reseach, 2026)
This study aims to analyze the internal oversight strategy in overseeing the accountability of free motor vehicle inspection services (KIR testing) at the UPT PKB of the Sidoarjo Regency Transportation Agency after the enactment of Law Number 1 of 2022 and Sidoarjo Regency Regional Regulation Number 1 of 2024. This retribution exemption policy institutionally shifts the organization's orientation from fulfilling regional fiscal targets to becoming a pure public value producer unit focused on transportation safety. However, the loss of budgetary control instruments creates new challenges in the form of internal moral hazard, such as the potential for decreased apparatus discipline and procedural negligence (rubber-stamping). Using a qualitative descriptive-analytical approach with a purposive sampling technique, this study collected data through in-depth interviews, observations, and documentation studies. The results show that the UPT PKB Sidoarjo successfully mitigated these risks through adaptive built-in control system engineering based on Bovens' three dimensions of public accountability. In the professional dimension, technical supervision is carried out through computerized testing equipment integrated with Electronic Test Pass Certificates (BLUE) and a digital Audit Trail system. In the administrative dimension, daily data reconciliation is carried out between the number of vehicles in the lane CCTV cameras and the issued BLUE certificates. Meanwhile, in the social dimension, a QR Code complaint channel is provided that is directly integrated with the Indonesian Ombudsman. This study concludes that the effectiveness of accountable and integrity-based toll-free services is largely determined by management's commitment to enforcing a strict digital monitoring strategy to reduce the subjective discretion of officers in the field.